2095. Associations between Invasive Aspergillosis and Cytomegalovirus Infections in Lung Transplant Recipients. (15th December 2022) - Wulff, Signe Marie; Perch, Micheal; Helweg-Larsen, Jannik; Bredahl, Pia; Arendrup, Maiken C; Lundgren, Jens; Helleberg, Marie; Crone, Cornelia G
Abstract: Background: Cytomegalovirus infection (CMV) and invasive aspergillosis (IA) are important causes of morbidity and mortality among lung transplant recipients (LTXr). These opportunistic infections share risk factors, but their interrelationship need further evaluation. Early diagnosis and treatment may improve outcomes. We examined incidence rates of CMV after IA and vice versa to assess whether screening for one of these infections may be indicated when the other is diagnosed. Methods: All adults receiving a lung transplant in Denmark from 2010 to 2019 were included and followed for 2 years after lung transplantation. IA was defined using the ISHLT criteria. Standardized screening for CMV and IA was performed during the study period (Figure 1). Incidence rates (IR) and incidence rate ratios (IRR) of CMV and IA was estimated by multivariate Poisson regression adjusted for time after transplantation (time updated), sex, age and high-risk CMV serostatus/IA high-risk condition. In analyses of CMV, we included IA as a time updated variable, and in analyses of IA, we included CMV as a time updated variable. Figure 1 Screening protocol for cytomegalovirus (CMV) and invasive aspergillosis following lung transplantation Valganciclovir prophylaxis was administered to patients with CMV serostatus D+/R−, D+/R+, and D−/R+ for three months after transplantation. In 2010-2016 voriconazole was administered as antifungal prophylaxis for all LTXr three months after transplantation. In 2016-2019 posaconazole and inhaled amphotericin B was administered for three months after transplantation for patients at high risk of IA. D, Donor; R, Recipient; PCR, Polymerase Chain Reaction; CMV, cytomegalovirus; BAL, bronchoalveolar lavage; Lung biopsy, transbronchial biopsy Results: A total of 295 LTXr with 351 person-years of follow-up (PYFU) for CMV and 440 PYFU for IA were included (Table 1). CMV and IA were diagnosed in 122 (41.4%) and 57 (19.3%) LTXr, respectively (Figure 2). IA diagnosis was proven in 20 and probable in 37 patients (Table 1). Among LTXr diagnosed with IA, 15.8% developed CMV within 3 months, IR 109 per 100 PYFU (95% CI 57-210) (Table 2). The median viral load at CMV diagnosis after IA was 2900 copies/mL (IQR 525-19000). The first 3 months following IA diagnosis there was an increased risk of CMV, although not statistically significant after adjustment for time after LTX with aIRR 1.60 (95% CI 0.80-3.20). Among LTXr diagnosed with CMV, 8.2% developed IA within 3 months, IR 40 per 100 PYFU (95% CI 22-75) (Table 2). In the first 3 months following CMV diagnosis, there was a significantly increased risk of IA, aIRR 2.97 (95% CI 1.47-6.00). Numbers needed to screen to diagnose one case of CMV following IA, and one case of IA following CMV were approximately 6 and 12, respectively. Table 1: Characteristics of lung transplant recipient and infectious outcomes, n (%) *IA high-risk conditions; **Number of patients negative in blood samples but positive in BAL samples (minimum >3000 CMV copies/mL). Invasive aspergillosis defined by the ISHLT criteria including anastomosis infection, tracheobronchitis and pneumonia. TX, Transplantation; COPD, Chronic obstructive pulmonary disease; CMV, cytomegalovirus; D, Donor; R, Recipient; BAL, Bronchoalveolar lavage. Table 2: Incidence rates and incidence rate ratios of cytomegalovirus (CMV) and invasive aspergillosis (IA) 1Adjusted for age >50 years, sex, and high-risk CMV serostatus. 2Adjusted for time after transplantation, age >50 years, sex, and high-risk CMV serostatus. 3Adjusted for age >50 years, sex, and IA high-risk underlying condition. 4Adjusted for time after transplantation, age >50 years, sex, and IA high-risk underlying condition. CMV, cytomegalovirus; IR, incidence rate; PYFU, Person-years of follow-up; IRR, incidence rate ratios; aIRR, adjusted incidence rate ratio; CI, confidence interval; TX, transplantation; IA, invasive aspergillosis. Figure 2: Kaplan-Meier survival estimates for CMV infection (A) and invasive aspergillosis (B) after lung transplantation Conclusion: Systematic screening for CMV following diagnosis of IA, and vice versa, may improve the timeliness of treatment and thereby outcomes for LTX recipients. Disclosures: Maiken C. Arendrup, DMSci, PhD, MD, Chiesi, Gilead: Honoraria|F2G, Cidara, Scynexis: Grant/Research Support Marie Helleberg, PhD, DMSc, AstraZeneca: Advisor/Consultant|Gilead: Advisor/Consultant|Gilead: Honoraria|GSK: Advisor/Consultant|GSK: Honoraria|Janssen: Advisor/Consultant|Roche: Advisor/Consultant|Sobi: Advisor/Consultant.